Implementation of Image Media to Increase Students' Interest in Learning Islamic Education at SD Negeri No.105404 Pekan Sialang Buah - Sumarno; Yanthy, Julya Dharma (MANDAILING GLOBAL EDUKASIA, 2024)
This Classroom Action Research was conducted to address the low learning interest of fourth-grade students at SDN No.105404 Pekan Sialang Buah in the subject matter of the stories of prophets and apostles. The lack of student enthusiasm, minimal active participation, and suboptimal learning outcomes indicated the need for an engaging instructional approach. The study aimed to enhance students' interest in learning through the use of picture media as a visual and attractive learning strategy. Implemented in two cycles consisting of planning, action, observation, and reflection stages, the research involved [number of students] as subjects. Data were collected using learning interest questionnaires administered before and after each cycle, along with classroom observations. The findings revealed a significant improvement in students' learning interest, as shown by increased questionnaire scores and more active participation during lessons. Picture media successfully captured students' attention, improved focus, and facilitated comprehension of storylines and characters within the religious narratives. The visual representation of the material made the learning process more enjoyable and meaningful. In conclusion, the use of picture media proved effective in increasing students’ interest in the stories of prophets and apostles and is recommended as an innovative alternative for teaching Islamic Religious Education, especially for narrative-based content.